2017
DOI: 10.1038/cgt.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Research on miRNA-195 and target gene CDK6 in oral verrucous carcinoma

Abstract: Oral verrucous carcinoma (OVC) is a verrucous variant of oral cavity squamous carcinoma (OSCC). The expression of miRNA from OVC and OSCC including their matched normal oral mucosa tissues was profiled through the Affymetrix GeneChip miRNA Arrays. TargetScan and miRanda databases were used to predict the target gene of miRNA-195. The quantitative real-time PCR was applied to validate the expression of miRNA-195. The expression of CDK6 was investigated by the quantitative real-time PCR and immunohistochemistry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…A study suggested a negative relationship between miR-195 and CDK6 and further verified that miR-195 and its target gene CDK6 could be regarded as potential diagnostic biomarkers and therapeutic targets of OVC. 146 These results suggested that miR-195 could serve as a potential therapeutic target and promising biomarker in head and neck cancer. Thus, miR-195 merits further exploration in future studies.…”
Section: Mir-195 In Various Cancersmentioning
confidence: 91%
“…A study suggested a negative relationship between miR-195 and CDK6 and further verified that miR-195 and its target gene CDK6 could be regarded as potential diagnostic biomarkers and therapeutic targets of OVC. 146 These results suggested that miR-195 could serve as a potential therapeutic target and promising biomarker in head and neck cancer. Thus, miR-195 merits further exploration in future studies.…”
Section: Mir-195 In Various Cancersmentioning
confidence: 91%
“…NUF2 is a direct target of miR-3613-3p which participate in cell proliferation and cell cycle in hepatocellular carcinoma. CDK6 has been found as a target of several miRNAs, including miRNA-195, miRNA-29c, miRNA-218, miRNA-504, and miR-6883, and linked to bladder cancer, colon cancer, oral verrucous carcinoma, and medulloblastoma 6167 . USP47 was found as a target of miRNA-204-5p and involves in gastric cancer cell proliferation 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the downregulation of miRNAs contributes to the pathogenesis of OVC. Specifically, miR-195 is found to be significantly downregulated in OVC [109] . miR-195 serves as either an oncogene or a tumor Figure 8.…”
Section: Malignant Cell Growthmentioning
confidence: 96%
“…miR-195 exerts its effects through various target genes, one of which is cdk6. cdk6 is activated in the G1 phase of the cellcycle and plays a role in the development of various cancers; cdk6 is found to be significantly upregulated in OVC [110] . This negative correlation between the expression of cdk6 and miR-195 in OVC serves as confirmation of the interaction between the two.…”
Section: Malignant Cell Growthmentioning
confidence: 99%